Pandangan M. Quraish Shihab tentang Posisi Alquran dalam Pengembangan Ilmu - Aprison, Wedra (Madania: Jurnal Kajian Keislaman, 2017)
The View of M. Quraish  Shihab View on the Position  of  the Quran in Science Development. The Moslem scholars disagree over the relationship between the Quran and science. Al-Ghazâlî, for example, states that all branches of science, both the already and the unknown, derived from the Quran. While Al-Syâthîbi ’s view is different from Al-Ghazâlî thus it needs to clearance the position of the Quran in the development of knowledge. The research question is how the position of the Quran in the development of science according to the view of M. Quraish Shihab? This study was conducted using a philosophical approach. The conclusion of this research is that the position of the Quran in the development of science more as an ethical basis rather than as a source of science or epistemological base. The Quran is a support for Moslem to seek, research, and develop science. It means that the Quran fills the axiology of scientific development.